NET PROFIT AND STOCK PRICE: EXPLORING THE MODERATING ROLE OF DIVIDEND PAYOUT RATIO IN IDX QUALITY 30 - Ulfida, Deafatunnizwa; Rizka, Nor Rahma; Izzadieny, Fitra; Rahmi, Audina (Worksheet : Jurnal Akuntansi, 2025)
This study investigates the impact of net profit on stock price with dividend payout ratio as moderating variable, recognizing that understanding the drivers of stock price is crucial for investors and financial analysts. The research utilizes multiple regression analysis to examine the direct effect of net profit on stock price and the moderating role of the dividend payout ratio. The results show that net profit has a positive and significant effect on stock price, supporting the hypothesis that higher profitability leads to increased stock valuation. However, the dividend payout ratio does not significantly moderate the relationship between net profit and stock price, indicating that it does not strengthen the effect of profitability on stock performance. These findings challenge the signaling theory, which suggests that dividend policies serve as a signal to investors. The implications of this research suggest that investors should focus on profitability as the primary indicator when evaluating stocks, while companies should prioritize improving profitability rather than relying on dividend policies to influence stock price. Future research should explore additional variables and apply broader data sets to further understand the relationship between financial performance and stock valuation.